“New Wave” in Children’s Literature of China during the 1980s - R.V. Zamilova (Ученые записки Казанского университета: Серия Гуманитарные науки, 2016)
The paper considers the period from 1978 to 1989, a rebirth, in the development of children’s literature of China. This stage, which was called “new wave”, is characterized by a number of significant events. Firstly, children’s literature wrenched free from the ideology of Maoism, which turned it into the disciplinary instrument only, and writers returned to the humanistic values of the May Fourth Movement. Secondly, the theoretical basis of children’s literature of China was formed. Its division in accordance with characteristics of the age and psychological development of the reader was carried out. Thirdly, many qualitative fiction works of various styles and thematic coverage were created during that period. They were focused on self-sufficient personality development. In this study, the works of Chinese researchers (Wang Quangen (王泉根), Wu Qinan (吴其南), Zhou Zuoren (周作人), Tang Rui (汤锐), etc.) that have not been previously translated into the Russian language.